2009
DOI: 10.1177/039463200902200303
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sclerosis and Cancer

Abstract: To review recent advances and current controversies on the association between systemic sclerosis (SSc) and cancer, PUBMED was searched from 1966 to the present using the terms: systemic sclerosis, cancer, morphoea, sclerotic diseases. Malignancies, mainly in lung and breast, coexist with idiopathic SSc or with SSc-like disorders, but not with localized forms of scleroderma (morphoea), with the exception of squamous cell carcinoma in patients with pansclerotic morphoea and skin ulcers. The mechanisms connectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
20
0
3
Order By: Relevance
“…While an increased risk of breast cancer was observed in several earlier studies, 11–14 our study found no increased risk of hormone‐related cancers, including breast cancer, among patients with systemic sclerosis. However, it cannot be ruled out that breast cancer may lead to sclerotic changes of the skin through a direct effect of the cancer or of the treatment 41 …”
Section: Discussionmentioning
confidence: 99%
“…While an increased risk of breast cancer was observed in several earlier studies, 11–14 our study found no increased risk of hormone‐related cancers, including breast cancer, among patients with systemic sclerosis. However, it cannot be ruled out that breast cancer may lead to sclerotic changes of the skin through a direct effect of the cancer or of the treatment 41 …”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy may be a trigger for pre-existing (asymptotic) systemic sclerosis, particularly when undergoing radiotherapy for breast cancer (15), as can treatment with certain chemotherapeutics (14). …”
Section: Discussionmentioning
confidence: 99%
“…Whether cancer is a risk factor or a trigger for morphea and systemic scleroderma is controversial. Lung and breast cancer seem at least to coexist with scleroderma [23,24]. …”
Section: Discussionmentioning
confidence: 99%